How the Students in Senior High School Maintain Their Foreign Language during Covid-19 Pandemic - Hamida Nur Rahmawati; Shinta Bekti Nugrahani; Ani Susanti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This paper focuses on observing how the students maintain their foreign language during Covid-19 pandemic. The survey of this paper was interviewed by questionnaire. There are 18 questions in which questions number 1-12 are the questions to collect the information about language that they used in their daily life and questions number 13-18 are questions about the technology or media that they used to study language. The result of the survey is that there are 5 students that answer the questions. From the data 83,3% they often used the local language for their daily language. The impact of coronavirus, they must study from home. They have some challenges studying foreign languages. The students need to maintain their foreign language during online learning.